Scale : the universal laws of life and death in organisms, cities and companies - West, Geoffrey, ....- (London : Orion Publishing, 2017)
Geoffrey West's research centres on a quest to find unifying principles and patterns connecting everything, from cells and ecosystems to cities, social networks and businesses.'An absolutely riveting read . . . groundbreaking' Marcus du Sautoy'This book will expand your thinking from three dimensions to four' Nassim Nicholas Taleb'Scale is a firework display of popular science' Niall Ferguson'This is an important and original book, of immense scope' Lord Martin Rees, Astronomer RoyalScale addresses big, urgent questions about global sustainability, population explosion, urbanization, ageing, cancer, human lifespans and the increasing pace of life, but also encourages us to question the world around us. Why can we live for 120 years but not for a thousand? Why does the pace of life continually increase? Why do mice live for just two or three years and elephants for up to 75? Why do companies behave like mice, and are they all destined to die? Do cities, companies and human beings have natural, pre-determined lifespans? Are we just a fascinating experiment in natural selection that is ultimately doomed to fail? And what is the origin of the magic number 4 that seems to determine much of physiology and life-history from birth to death?
Keywords: Filosofie ; maatschappij